Labour-Market Reform, Skill-Based Exports and Employment: Some Unconventional Results Under Finite Change in General Equilibrium - Rashmi Ahuja; Shrimoyee Ganguly; Rajat Acharyya; Sugata Marjit (CESifo GmbH, 2024)
This paper highlights the critical role that demand-shock and policy-shock induced finite changes play for the unconventional employment consequences of such shocks at a general equilibrium of a multi-sector competitive economy. A labour market reform that lowers the institutional costs of hiring workers for the firms in traditional import-competing sectors, and a secular rise in world-demand for non-traditional skill-based exports that raises its world price, are the two specific and pertinent shocks that we consider. We show a small or minor labour market reform can paradoxically result in a larger unemployment of unskilled labour due to one of the import-competing sectors shutting down as it fails to cope up with the import competition. Subsequent reforms however raises aggregate employment. Thus, we may have a J-curve like employment response to gradual and sequential labour market reforms. A big-bang approach to policy reform may work better by avoiding such an initial adverse employment effect. Our findings add to the growing body of literature that challenges conventional wisdom about labour market flexibility having favourable impact on employment. These also emphasize the need for policymakers to carefully consider the broader economic context and potential sectoral shifts when designing labour market reforms. On the other hand, contrary to apprehensions, we show that global-demand-driven hike in the world price of the skill-based export goods may initially raise aggregate employment of unskilled workers due to a similar finite change.
Keywords: D50; F16; J32; J64; 330; labour market reforms; finite change; skilled-based exports; employment